Numerical simulation and topology optimization of slider air bearing - Li, Qiang (2008)
Since the first commercial hard disk drive was developed in 1956, the stability of the flying attitude is always an important factor to be considered in the slider air bearing design. The objective of this dissertation is to develop an efficient computational modeling technique for simulating the air bearing slider (ABS) in hard disk drives and ultimately develop an effective topology optimization methodology to systematically and automatically design the air bearing slider with a target of achieving a near-constant flying attitude when the slider moves over the surface of the hard disk drive. Although sizing and shape optimization approaches have been explored for optimal design of the slider air bearing, those previous works were mainly restricted to variation of simple geometric parameters. This dissertation is attempted to propose a true and complete topology optimization approach for the slider air bearing design for potential practical applications.